Groundwater and hydrogeochemical patterns of Campi Flegrei active caldera (southern Italy) for volcanic hazard assessment - V. Allocca; P. Allocca; R. Avino; S. Caliro; S. Cerrone; S. Coda; D. Cusano; M. A. Di Vito; D. Lepore; P. Petrone; E. Schioppa; P. De Vita (Natural Hazards, 2026)
The paper presents a comprehensive hydrogeochemical characterization of the volcanic aquifer of the Campi Flegrei caldera (hereafter CFc) (southern Italy). This highly urbanized and restless volcanic area is characterized by recurring bradyseismic phenomena and low- to medium-energy seismicity as well as by anomalous groundwater patterns whose study can be considered an extension of the current volcanic monitoring aimed at hazard assessment. Accordingly, this research is based on the analysis of hydrogeological and hydrogeochemical unpublished datasets collected over the last decades including well censuses, water table surveys carried out in the period 1985–2013 and reconstructions of groundwater flow and hydrogeochemical patterns. The identification of hydrostratigraphic units and their hydraulic behavior was supported with recent advances in the volcano-stratigraphic and volcano-tectonic framework of the CFc. Moreover, hydrogeochemical data provided further insights into groundwater circulation and its links to hydrothermal activity. Results show that groundwater circulation inside the CFc is independent from the surrounding aquifers, forming a dome-shaped piezometric structure with radial flow. Two groundwater basins are distinguished, separated by a divide roughly corresponding to the northern rim of the Neapolitan Yellow Tuff (NYT) caldera: a northern one with normal temperatures and bicarbonate-rich waters, and a southern one with warmer, chloride- and magnesium-rich waters influenced by hydrothermal activity and seawater mixing. The findings of this study provide insights into groundwater–hydrothermal interactions in the CFc, supporting the design of a hydrogeological and hydrogeochemical monitoring network, based on selected wells, for the detection of potential precursors of changes in volcanic and bradyseismic activities.

Last interglacial relative sea-level changes at Myrtle Beach, South Carolina - S. Dean; N. Georgiou; R. Poirier; W.R. Doar; D. Brill; D. Chauveau; C. Cerrone; J. Austermann; A. Rovere (Quaternary Science Reviews, 2026)